2015
DOI: 10.1038/nrgastro.2015.36
|View full text |Cite
|
Sign up to set email alerts
|

Mixed HCV infection and reinfection in people who inject drugs—impact on therapy

Abstract: The majority of new and existing cases of HCV infection in high-income countries occur among people who inject drugs (PWID). Ongoing high-risk behaviours can lead to HCV re-exposure, resulting in mixed HCV infection and reinfection. Assays used to screen for mixed infection vary widely in sensitivity, particularly with respect to their capacity for detecting minor variants (<20% of the viral population). The prevalence of mixed infection among PWID ranges from 14% to 39% when sensitive assays are used. Mixed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 144 publications
(262 reference statements)
3
77
0
Order By: Relevance
“…However, other studies suggested that previous spontaneous clearance of HCV infection might not reduce the risk of new infection [142]. Ongoing highrisk behaviors among PWID can lead to repeated exposure to HCV, resulting in reinfection [143]. Although reinfection is common, it does not always lead to persistent infection.…”
Section: Reinfection In Pwidmentioning
confidence: 98%
See 1 more Smart Citation
“…However, other studies suggested that previous spontaneous clearance of HCV infection might not reduce the risk of new infection [142]. Ongoing highrisk behaviors among PWID can lead to repeated exposure to HCV, resulting in reinfection [143]. Although reinfection is common, it does not always lead to persistent infection.…”
Section: Reinfection In Pwidmentioning
confidence: 98%
“…However, the rate of HCV reinfection might be as low as 0-5 cases per 100 person-years, even among persons who continue injected drug use during and after treatment [143,145,146]. Due to the low reinfection rate and potential clearance after reinfection, antiviral treatment should not be withheld for these populations.…”
Section: Reinfection In Pwidmentioning
confidence: 99%
“…Indeed, dual or MI are rarely detected by standard sequencing, because the simultaneous presence of large quantities of different viruses is usually a transient occurrence. Moreover, standard sequencing can generally detect the prevalent virus; in fact only HCV variants present at the prevalence of > 20% (9). In a short period, one strain is deemed to prevail, either for a less efficient host immunological pressure, or for an intrinsic major fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Blackard J et al defined coinfection as "infection with > 2 HCV heterologous HCVs simultaneously or within a very narrow period before infection with the first HCV as resulted in an immunological response to that virus", superinfection as "infection with a second HCV after the establishment of persistent HCV infection and development of an immunological response to the first virus", and reinfection as "primary infection that is completely cleared virologically prior to a subsequent, secondary infection with either a homologous or a heterologous HCV" (7). Their prevalence is reported from 5% to 39% in individuals with HCV infection, and considerably higher in injection drug user (IDU) cohorts, or in prison settings than in other at-risk groups such as multiple blood recipients and patients undergoing dialysis (1,8,9). It is suggested that MI can impact the course of the disease, either by boosting hepatocellular injury or by increasing the frequency of exacerbations (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation